West Nile Virus Population Structure, Injury, and Interferon-Stimulated Gene Expression in the Brain From a Fatal Case of Encephalitis. (20th November 2015) - Grubaugh, Nathan D.; Massey, Aaron; Shives, Katherine D.; Stenglein, Mark D.; Ebel, Gregory D.; Beckham, J. David
Abstract: Background.  West Nile virus (WNV) infection in humans can result in severe, acute encephalitis typically involving subcortical gray matter brain regions. West Nile virus replication within specific human brain regions from a human case of acute encephalitis has not been studied. Methods.  We describe a fatal case of WNV encephalitis in which we obtained tissue from specific brain regions at autopsy to evaluate viral-host interactions using next-generation sequencing and immunohistochemistry analysis. Results.  We found that WNV populations in the injured subcortical brain regions exhibited increased amino acid variation and increased expression of specific interferon genes compared with cortical tissues despite similar viral burden. Conclusions.  These observational, patient-based data suggest that neuronal injury and the strength of viral selection pressure may be associated with the level of the innate immune responses. Further studies in human and animal models evaluating the role of innate immune responses on injury patterns and viral selection pressure are needed.